Keragaman Avifauna pada Lahan Bekas Tambang Emas PT Kelian Equatorial Mining, Kutai Barat Kalimantan Timur (Variety of Avifauna on Land Ex-Gold Mining PT Kelian Equatorial Mining West Kutai, East Kalimantan) - Chandra Boer (Institut Pertanian Bogor (IPB University), 2009)
The presence of birds’ species on the land ex-gold mining in PT Kelian Equatorial Mining West Kutai, East Kalimantan becomes a good indication for the future of the rehabilitation area. The existence of natural forest in surrounding of rehabilitation area is a source of species for this rehabilitation area. The difference and the similarity of species between natural forest (Dam Namuk) and rehabilitation area (Lower Nakan) show that the primary species start doing occupation in rehabilitation area. The monitoring to the selected species (dominant or rare) needs to be implemented in the future to make sure the success of the rehabilitation area as a good habitat provider for many birds’ species.Keywords: avifauna, rehabilitation, natural forest, habitat